Accounting students' and employers' perceptions on employability skills in the SEE country - Atanasko Atanasovski; Marina Trpeska; Zorica Bozinovska Lazarevska (European Financial and Accounting Journal, 2019)
Accounting education at the university level in developing SEE countries has often been criticised for the inability to develop essential skills of graduates necessary for a career in professional accountancy in the 21st century. Our research study presents the results of a survey among students enrolled to an accounting degree program and employers for their perceived importance of a wide range of generic and technical skills for successful entrance to the profession. The study also investigated perceived effectiveness of the university accounting education to develop important skills at an appropriate level. The results indicated agreement between the two respondent groups in respect of the greater importance of generic skills, where students gave more weight to personal skills of time management, good presentation and characteristics of self-confidence, motivation and self-promotion. Employers valued more oral communication, knowledge of foreign languages, ethical attitude and credibility and commitment to life-long learning. The employers and students agreed that education process and program need improvements in order to allow for better development of technical and generic skills among successful graduates.
Keywords: J24; M41; 650; Expectation gap; Generic skills; Students employability; Students' perceptions